Fontes de Nitrogênio no Cultivo de Milho em Sistema Plantio Direto: avaliação econômica e produtividade - Portugal, André Vilela (2012)
In corn crop, nitrogen is the nutrient most required, which further affects their productivity and which further onerous the cost of production. The purpose of this study was to evaluate sources of nitrogen in corn growth in tillage system. The experiment was conducted at the Vitoria farm, located in the city of Alfenas - MG, in a area of the first year of tillage system. For this, it was used the transgenic corn hybrid Impact of Syngenta, and it was employed random blocks design experimental, with7 treatments and 4 replications, totaling 28 plots. The treatments applied consisted: Control (without nitrogen in coverage); 100 Kg ha-1 of nitrogen in coverage, with ammonium nitrate, without incorporation; 100 Kg ha-1 of nitrogen in coverage, with urea, without incorporation; 100 Kg ha-1 of nitrogen in coverage, with urea and incorporation; 100 Kg ha-1 of nitrogen in coverage, with ammonium sulfate, without incorporation; 100 Kg ha-1 of nitrogen in seeding, with controlled release fertilizer, without incorporation; 50 Kg ha-1 of nitrogen in seeding, with controlled release fertilizer, without incorporation. The assessments of the experiment were performed, after 154 days, according to the parameters: grains productivity, number of grain rows per cob, weight of 1,000 grains, number of grains/row in each cob and number of grains per cob. With this study it can conclude that: the common urea, ammonium sulfate and ammonium nitrate showed similar performance and economic returns in corn crop tillage system; the incorporation of urea did not improve grain productivity and components production in corn growth in tillage system, the controlled release fertilizer is not feasible from an economic standpoint in corn growth in tillage system.